A new species of Notonyx A. Milne-Edwards, 1873 (Crustacea: Decapoda: Brachyura: Goneplacidae) from the Philippines - Clark, Paul F.; Ng, Peter K. L. (Zootaxa, 2011)
A new species of Notonyx A. Milne-Edwards, 1873 (Crustacea: Brachyura: Goneplacidae) is described from the Sulu Archipelago, southern Philippines. It is closest to the type species, N. nitidus A. Milne-Edwards, 1873, but differs in the form of the abdomen and third maxillipeds, and most significantly, in the structures of the male first and second gonopods.